RELEVANSI KURIKULUM MERDEKA DALAM PERSPEKTIF PENDIDIKAN ISLAM SYED MUHAMMAD NAQUIB AL- ATTAS - Afandi Afandi; Muksin Muksin; Risa Fadatul M. (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2023)
Education in Indonesia has undergone curriculum changes caused by the ever-changing and developing state of society, so that many new life problems are needed, so the Ministry of Education and Culture launched the Independent Curriculum and researchers associated it with Syed Muhammad Naquib al-Attas, as a figure who has a well-known and brilliant Islamic education thought and this research adheres to the rationale contained in it. This research uses a descriptive qualitative approach to content analysis with the type of library research, collecting data using documentation methods or records as data sources. From the results of the discussion and research, it was concluded that the Islamic education thought of Syed Muhammad Naquib alAttas and its relevance to the Independent Curriculum is first, the concept of ta'dib is in line with the principles of designing the Independent Curriculum and the development policy of the Independent Curriculum. Second, the objectives of al-Attas' Islamic education are aligned with the Merdeka Curriculum.